Better Mental Component of Quality of Life in Amputee - GR Karami; Kh Ahmadi; V Nejati; M Masumi (Tehran University of Medical Sciences, 2012)
Background: Assessment of quality of life can promote health services. The purpose of this study was evaluation of health related quality of life in lower limbs amputee veterans of Iran. Methods: In the present cross sectional study, we compared 38 lower limbs amputee veterans with 50 normal healthy subjects with SF36 questioner in face-to-face interview. Results: Amputees had significantly lower grade than normal subject did in role physical (P < 0.01) and were better than normal subjects in vitality (P < 0.001) and mental health (P < 0.01). As a whole, amputees have higher in mental summary component of quality of life (P < 0.05) and lower in physical component of quality of life (P < 0.01). Conclusion: Diminishing the demand and improving social support of amputee veterans might be considered as high grade in mental summary component of their quality of life.